Four new taxa of Ilyonectria and Thelonectria (Nectriaceae) revealed by morphology and combined ITS and β-tubulin sequence data - Zeng, Zhao-Qing; Zhuang, Wen-Ying (Phytotaxa, 2013)
Thelonectria beijingensis sp. nov. is characterized by a distinct perithecial wall of textura epidermoidea mixed with textura intricata, purple to brown colonies, curved cylindrical macroconidia with rounded ends, ellipsoid to rod-shaped microconidia, and lacking chlamydospores. Thelonectria yunnanica sp. nov. is distinguished by a three layered perithecial wall with a palisade of short hyphae that are perpendicular to the outer surface, white colonies, elliptical-fusoid to rod-shaped microconidia with rounded ends and lacking chlamydospores. Neonectria hubeiensis and N. sinensis are transferred to Ilyonectria and Thelonectria, respectively. Distinctions between the new taxa and their close relatives are discussed based on morphology and the combined sequence data of nuclear ribosomal DNA ITS1-5.8S-ITS2 and partial β-tubulin gene.